Dalita-Adibasi-samkhyakaghu abadamana o uttarana (Kalakātā : Laki Pabalisarsa, 2016)
Articles on the social condition of Dalits, Adivasis and religious minorities of India.
In Bengali.
Keywords: Adivasis -- India -- Social conditions; Adivasis -- Social conditions; India